Practical Training Report (ADS 667) Sarawak Plantation Berhad Miri (SPB) / Roziana Bahjam - Bahjam, Roziana (University Technology MARA Sarawak, 2015)
Sarawak Plantation Berhad or known as SPB was incorporated in Malaysia on 28 October 1997 as a private limited company under the name of Sarawak Plantation Sdn. Bhd and commenced business in the same year. After three years this company was converted into a public company on the 1st February 2000 and it assumed as the present name. Under Sarawak Land Development Board's (SLDB), SPB has been specially incorporated as the vehicle company for the privatization as assets. Moreover, Sarawak Land Development Board (SLDB) is a body corporate established by the Sarawak Land Development Order 1972 and also under the Land Development Ordinance 1956. The privatization of SLDB’s assets, comprising oil palm plantations, milling facilities and related assets, was affected in 1997 through the transfer of SLDB’s assets to SPB Group (comprising SPB and its subsidiaries). With all this privatization, all principal assets of SLDB are owned and managed by SPB and certain of its subsidiaries.